"We are becoming older women and then we have two stigmas": voicing women's biopsychosocial health issues as they age with HIV. (3rd July 2020) - Marg, Logan Z.; Ruiz, Griselda; Chagolla, Fidel; Cabral, Alejandra; Taylor, Jeff; Christensen, Chris; Martin, Marjorie; Picou, Bridgette; Brown, Brandon
ABSTRACT: In April 2019, nine older women (age 50+) living with HIV in Palm Springs, California, participated in a 90-minute focus group to identify their major health issues, strengths, and HIV and aging-related health priorities. Using the rigorous and accelerated data reduction (RADaR) technique, we identified four major themes: (1) mental health, (2) HIV comorbidities, (3) social determinants of health, and (4) resiliencies. These results reinforce the need to conduct additional research focused on women aging with HIV, an understudied population that requires more effective, tailored interventions to promote better quality of life and healthy aging.